Analisis Yuridis terhadap Pelaksanaan Putusan Arbitrase Komersial Internasional di Indonesia Berdasarkan Undang-Undang Nomor 30 Tahun 1999 - Putri Apri Amanda; Hudi Yusuf (Media Hukum Indonesia (MHI), 2026)
The increasing volume of international trade has encouraged the use of arbitration as a dispute resolution mechanism that is considered more effective, efficient, and capable of providing greater legal certainty than litigation. This study aims to analyze the mechanism for the enforcement of international commercial arbitral awards in Indonesia under Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, as well as to examine the enforcement of an arbitral award in the dispute between the Ministry of Defense of the Republic of Indonesia and Navayo International AG. This research employs a normative legal research method using both the statutory approach and the case approach. The data used are secondary data obtained through library research, including legislation, books, scholarly journals, and other relevant legal documents, which are analyzed using a qualitative method. The findings indicate that the enforcement of international commercial arbitral awards in Indonesia has a clear legal basis under Law Number 30 of 1999. However, such enforcement must satisfy the statutory requirements for recognition and enforcement, including compliance with the public policy exception. In the dispute between the Ministry of Defense of the Republic of Indonesia and Navayo International AG, the enforcement of the arbitral award demonstrates legal complexities due to the involvement of a state institution. This situation requires a balance between Indonesia's obligations under international law and the protection of its national interests